Japanese Science Policies and Their Impacts on Scientific Research - Akira Muto (Publications, 2025)
Innovation in science and technology arises from balanced supports for basic research, applied research, and societal implementation. However, changes in Japanese science policy that shifts toward top–down, evaluation-based, and competitive funding practices appear to have undermined Japan’s long-term research sustainability and innovation potential. The “selection and concentration” strategy (prioritization of specific research areas) and “competition principle”, combined with persistent reduction in Management Expenses Grants, have significantly altered Japan’s research environment for the worse. Together with these policy changes, the introduction of fixed-term contracts in academia has increased instability at both the institutional and the individual levels and has diminished the time and resources available for long-term basic research. Academic careers in science have become less attractive, as evidenced by declining doctoral student enrollment. These changes threaten the potential for scientific discoveries that lead to innovation. Although initiatives such as the introduction of University Research Administrators (URAs) have been implemented to support researchers, such efforts remain insufficient to counterbalance the systemic challenges faced by Japan’s research ecosystem. To re-establish a stable research environment, rethinking the strategy may be necessary, including restoration of stable institutional funding, sustainable career pathways, and balanced funding allocation to basic science that foster seeds for future innovation.